PLURAL FORMS IN PERSIAN AND DARI LANGUAGES - Alimova, Kholida (Foreign Languages ​​in Uzbekistan (JOURNALFLEDU.COM), 2024)
The modern Persian and Dari languages express the categories of nouns through morphology, specifically the plural and the postpositive article. This article investigates the plural forms and their functioning in these languages. The systematisation of plural forms in Persian and Dari spurred attempts to distinguish types and varieties. Currently, the division of all plural forms into "correct" and “incorrect” is preferred. There are two correct plural forms in Persian: one with the suffix “ان “and the other with “ها“. The latter is more commonly used and can form the plural of any noun. The former is limited to a specific group of nouns, especially personal names. Historically, “ها “has been more prevalent than “ان“, even though the latter is the more ancient suffix. In early New Persian, “ان “was actually more common than “ها“. While the suffix “ها “is considered universal in Modern Persian and Dari, the analysis of the materials indicates that the issue regarding the stylistic differentiation of the plural forms is intricate. Additionally, Arabic has lent irregular plural forms to the language. For some scholars, “irregular” is synonymous with “broken” plural forms of Arabic words. Statistical analysis results demonstrate that the “correct” and “incorrect” plural forms in modern Persian and Dari may function as synonyms or diverge semantically and stylistically in word combinations. Additionally, the transformation of broken plural Arabic words into words with abstract or alternative meanings has been observed.
Keywords: Persian and Dari languages; plural forms; “correct” and “incorrect” plural forms; broken plural form; statistical analysis